EFEKTIVITAS BIOPESTISIDA BACILLUS SUBTILIS BNt 8 DAN PESTISIDA NABATI UNTUK PENGENDALIAN PENYAKIT HAWAR PELEPAH DAN UPIH DAUN JAGUNG - Djaenuddin, Nurasiah; Muis, Amran (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Effectiveness of the biopesticide of Bacillus subtilis BNt 8 and botanical pesticide in controlling banded leaf and sheath blight disease on maize. Banded leaf and sheath blight disease (BLSB) caused by the fungus Rhizoctonia solani is difficult to control because it pertained soil borne fungus that can survive in a long time in the soil. Control the disease with synthetic pesticide causing contamination to the environment, so that an environmentally friendly alternative control is needed. This study aimed to obtain a Bacillus subtilis formulation as biological agents and selected botanical pesticides that effective to control BLSB in the field. The study was conducted at the Plant Pathology Laboratory of Indonesia Cereals Research Institutein Maros and at the Bajeng Experimental Farm in Gowa, held from February to August 2015. The reatments consists of several botanical pesticides, B. subtilis formulation, a synthetic fungicide, positive and negative controls. In vitro test was inhibition test between botanical pesticide with R. solani and antagonistic test between the B. subtilis and botanical pesticides, each of them consists of 6 treatments and 3 replications, while the field activity consists of test of effectiveness of single treatment and combination between B. subtilis formulation and botanical pesticides. The results showed that combination of formulated B. subtilis with botanical pesticide of cloves leaves, betel leaves, and turmeric were not significantly different from single treatment of formulated B. subtilis and botanical pesticides. Formulated B. subtilis suppressed the severity of BLSB as much as 39.1% and yield reached 8.4 t/ha.